Wisdom Has Built Her House - Doherty, M. J. (Cistercian studies quarterly, 2001)
Reviews the book 'Wisdom Has Built Her House: Studies on the Figure of Sophia in the Bible,' translated by Linda M. Maloney and William McDonough.